4C.09: EFFECT OF ANGII-INDUCED HYPERTENSION AND ANTIHYPERTENSIVE TREATMENT ON PATHOLOGICAL CHANGES IN A MOUSE MODEL FOR ALZHEIMER'S DISEASE. (June 2015) - Wiesmann, M.; Zerbi, V.; Roelofs, M.; Van Der Lugt, R.; Heerschap, A.; Claassen, J.A.H.R.; Kiliaan, A.J.
Abstract : Objective: Hypertension is a risk factor for Alzheimer's disease (AD). It is a treatable condition which opens important avenues for prevention of AD. Elevated angiotensin II (AngII) is an important cause of essential hypertension and has deleterious effects on endothelial function and cerebral blood flow (CBF). In this study we therefore investigated the interaction between AngII, systolic blood pressure (SBP), and MRI-measurements in the APPswe/PS1[Delta]E9 (APP/PS1) mouse model of AD. Design and method: We studied the effect of 2 months of induced hypertension (AngII-infusion using osmotic micropumps, vs saline (sal) as control) and, subsequently (after 1 month of induced hypertension) the effect of treatment (vs placebo) with antihypertensive (eprosartan mesylate (EM), 0.35 mg/Kg vs water) on SBP and metabolite levels, functional and neuronal connectivity and CBF in 10 months-old wildtype C57bl6/j (WT) and APP/PS1 mice. SBP was monitored twice a month via tail cuff plethysmography. RsfMRI, DTI, MRS, FAIR-ASL were measured on the 11.7T magnet (Bruker BioSpec). Results: In this study, chronic AngII-infusion increased BP in both transgenic and WT mice, while at 12-Month under AngII-infusion APP/PS1 mice had a higher SBP than WT mice. Furthermore, only in hypertensive AD mice cortical CBF was lowered compared to hypertensive WT mice. Additional data will be presented on the impact of AngII-induced hypertension and subsequent treatment with EM on Aβ-pathology, cognition, metabolite levels, structural and functional connectivity. Conclusions: Together, these data suggest an interaction between APP/PS1 induced pathologies, SBP, and antihypertensive treatment. Our results also reveal an association between hypertension (AngII), APP/PS1 and CBF.